Risk and reliability of exploration methods used to define a heavy mineral sand deposit in Kwa-Zulu Natal, South Africa - Camisani-Calzolari, Ferdinando Roux (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.